Left ventricular mechanical dyssynchrony in patients with impaired left ventricular function undergoing gated SPECT myocardial perfusion imaging - Ferreira, Maria João Vidigal (2013)
Introduction: Gated SPECT myocardial perfusion imaging (MPI) has been used to quantify mechanical dyssynchrony. Mechanical dyssynchrony appears to be related to response to cardiac resynchronization therapy. Objective: To evaluate the presence and predictors of mechanical dyssynchrony in patients with impaired left ventricular function (LVEF) ≤50%. Methods: The study included 143 consecutive patients referred for gated SPECT MPI with LVEF ≤50%. Gated SPECT MPI was performed according to a stress/rest protocol acquiring images with Tc 99m-tetrofosmin. Emory Cardiac Toolbox software was used for phase analysis and a standard deviation (SD) ≥43◦ was considered to indicate mechanical dyssynchrony. Results: Mechanical dyssynchrony was present in 53.1% of the patients. Its predictors were diabetes (OR 2.0, p≤0.05), summed stress score (OR 1.1, p≤0.0005), summed rest score (OR 1.1, p≤0.0001), end-diastolic volume (OR 1.0, p≤0.0001), LVEF (OR 0.9, p≤0.0001), LVEF ≤35% (OR 3.1, p≤0.005) and LVEF ≤35% and QRS ≥120 ms (OR 3.5, p≤0.05). In this study QRS width and QRS ≥120 ms were not predictors of mechanical dyssynchrony. Conclusions: Myocardial perfusion imaging can be used to assess mechanical dyssynchrony. In patients with impaired ventricular function mechanical dyssynchrony was highly prevalent and was related to parameters of left ventricular function and perfusion.